Synergistic CuCo2O4/MWCNT nanocomposites: advanced electrode materials for energy storage and catalysis applications - Waseem Abbas; Muhammad Irfan; Muhammad Babur; Muhammad Ehsan Mazhar; Javed Ahmad; Komal Ali Rao; Saqlain Haider; Hassan Ali; Muhammad Imtiaz; Muhammad Imran (Journal of Materials Science: Materials in Engineering)
Abstract The CuCo2O4 and CuCo2O4/MWCNT nanocomposites were synthesized using hydrothermal techniques as an electrode material for supercapacitor applications. Structural characterization, including XRD, SEM, and EDX, confirmed the successful fabrication of nanocomposites. Electrochemical analysis revealed that CuCo2O4/MWCNTs exhibit excellent oxygen (OER) and hydrogen (HER) evolution catalytic activity, with enhanced cyclic stability, high-rate capability, and better specific capacitance compared to pure CuCo2O4 electrodes. The synergistic interaction between CuCo2O4 and MWCNTs significantly improves electrochemical performance, highlighting the potential of these nanocomposites as an electrode material for energy storage and electrocatalytic applications.